Snapper rest where they see best: visually mediated choice behaviour of Australasian snapper (Chrysophrys auratus). Issue 1 (2nd January 2017) - Robinson, Esme; Jerrett, Alistair; Black, Suzy; Davison, William
Abstract: The sensory physiology and behaviour of many fish species are strongly affected by light. This short study demonstrates that in the Australasian snapper ( Chrysophrys auratus ) absolute light intensity governs visual acuity and also guides preference behaviour, with fish choosing to 'rest where they see best'. Use of the optomotor response to test visual acuity at four light intensities (0.01, 0.05, 1 and 3 μmol s −1 m 2 ), showed that visual acuity (measured as directional bias) was best at a light intensity of 0.05 μmol s −1 m 2 (84.9% directional bias), but weakened at the highest and lowest light intensity (41.1 and 35.3%). When provided with a choice of the same four light environments fish also spent most time in the 0.05 μmol s −1 m 2 light environment, while the highest and lowest intensity light environments were usually avoided. Acclimated light intensity (that is daytime light intensity of the home aquarium) was also 0.05 μmol s −1 m 2 . By selecting an environment where visual function is optimised, C. auratus are also optimising the ability to search for prey and to detect predators . The results are discussed with reference to habitat utilisation and thoughts for trawl fishing practices.